ERCP combined with SpyGlass DS direct visualization electrohydraulic lithotripsy in treatment of difficult bile duct stones - SHI Jiali, CHENG Sile, JIN Hangbin, ZHANG Xiaofeng (Waike lilun yu shijian, 2022)
Objective To investigate the efficacy and safety of endosocopic retrograde cholangiopancreatography (ERCP) combined with SpyGlass DS direct visualization electrohydraulic lithotripsy in the treatment of difficult bile duct stones. Methods A total of 35 patients with difficult bile duct stones in Hangzhou First People′s Hospital undergoing SpyGlass DS direct visualization electrohydraulic lithotripsy from January 2020 to February 2022 were enrolled. Clinical data were collected to analyze the success rate of lithotripsy, stone clearance, and single-session stone clearance with post ERCP complication rate, hospital stay after ERCP, and ERCP time. Results There were 34 (97.1%) patients with successful SpyGlass DS lithotripsy, One patient underwent incomplete electrohydraulic lithotripsy supplemented with extracorporeal shock wave lithotripsy. ERCP time was(77±13.1) min. All patients achieved stone clearance and single-session stone clearance was achieved in 29(82.9%) patients. Two patients with acute cholangitis and acute pancreatitis were found respectively and ERCP complication 5.7%. Hospital stay after ERCP was(6.3±3.7) days. Conclusions ERCP combined with SpyGlass DS-guided electrohydraulic lithotripsy would be safe and feasible in the treatment of difficult bile duct stones.